Perceived changes in the mental well‐being among Nigerians due to Ramadan Intermittent Fasting during the COVID‐19 pandemic - Sahabi Kabir Sulaiman; Fatimah Isma'il Tsiga‐Ahmed; Teresa Arora; MoezAlIslam E. Faris; Muhammad Sale Musa; Yesir Adeyemi Kareem; Farouq Muhammad Dayyab; Aminu Hussein; Shehu Sale; Syed Fahad Javaid; Moien AB Khan (Brain and Behavior, 2023)
Abstract Introduction Muslims fast every year during the month of Ramadan from dawn until dusk. This study examined mental well‐being and correlating factors among Nigerian adults who observed Ramadan intermittent fasting (RIF). Methods A validated generalized anxiety disorder‐2 and Patient Health Questionnaire‐2, the four‐item spiritual well‐being index, and the Islamic intrinsic religiosity questionnaire were used to collect data about mental well‐being (depression, anxiety), spirituality, and intrinsic religiosity through a web‐based survey between the May 9, 2021 (27th of Ramadan, 1442) and the June 4, 2021 (29th of Shawwal, 1442). We studied the mental well‐being of respondents over a period of 4 weeks before Ramadan (BR) and during the 4 weeks of Ramadan between the April 12, 2021 and the May 12, 2021(DR). Multinomial regression analysis was used to determine the factors associated with depression and anxiety. This research did not receive any grant or funding. Results A total of 770 adult Nigerians who observed RIF study were included in this cross‐sectional study. When compared to mental well‐being BR, observing RIF by Nigerian adult respondents was associated with a significant improvement in their mental well‐being. A higher proportion of respondents felt less depressed DR (61.3% vs. 56.5%. < .001). Interest and pleasure in doing things improved DR than BR (p= 0.007) and respondents felt less nervous and anxious (60.7% vs. 57.1%, respectively; p <.001). Mental well‐being was independently associated with sociodemographic characteristics, physical activity, and perceived relationships. Conclusions This study found significant improvement in mental well‐being DR compared to BR despite the ongoing COVID‐19 pandemic. The effect of RIF on mental well‐being needs further research with multicentric studies among different sets of ethnic populations.